EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN PERMAINAN BINGO TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA SEKOLAH DASAR - Putri Cahyaning Negari; Hamidaturrohmah (Universitas Islam Raden Rahmat Malang, 2026)
The research is grounded in the issue of unsatisfactory learning outcomes among fourth-grade students at SD Negeri 1 Bringin on the topic of understanding the surrounding environment, as indicated by the average score below the Minimum Learning Achievement Criteria (KKTP). The research was conducted to evaluate how effective the Problem Based Learning model, combined with a Bingo game, is in enhancing students’ learning outcomes. It applied a quantitative approach, utilizing a pre-experimental method with a One Group Pretest–Posttest design. The participants consisted of 27 fourth-grade students. The data were obtained using pretest and posttest instruments, then analyzed by applying the Shapiro–Wilk test for normality and a paired sample t-test, supported by the Jamovi software. The study demonstrated that the mean score rose from 58.9 during the pretest to 76.1 in the posttest phase. The analysis resulted in t (26) = -5.76 with p < .001, confirming a meaningful difference between the two score distributions. The obtained Cohen’s d value of -1.11 reflects a substantial effect size. This evidence indicates that the use of Problem-Based Learning combined with a Bingo game is effective in improving students’ learning outcomes in Pancasila Education.